Perilaku menyimpang dalam perspektif sosiologis - Suyato, Suyato (Jurnal Civics: Media Kajian Kewarganegaraan, 2005)
Discourse of deviant behavior becomes difficult because of its complexity and relativity. Its complexity stems from the facts that there are many concepts should be considered, namely medical concepts, legal aspects, and morals issues. Its relativity comes from the facts that there are many perspectives, such as cross-cultural perspectives, subculture variations, ecological context, variation over time, and situational aspects. Sociologists have been made explanation on deviant behavior but not yet comprehensive. Sociological perspectives on deviant behavior can be categorized as structural functional theory, symbolic interaction theories, and conflict theory. Each of them tries to explain major question, basic assumption, and causes of deviance by using its own perspective. For example, control theory has been emphasis that because the lack of strong tied (legal or social) from others, individual tends to conduct defiantly. Sociologists also has been tried to comprehend ways people neutralize their misbehavior. Using economic perspective and control theory to eliminated corruption conducted by apparatus in district development program as an example, this article concluded that it is needed to make a comprehensive perspective in solving deviant behavior problems, such as corruption.